Methodological considerations and proposed integrated legend for anthropogenic geomorphological mapping - Barbosa, Tamires Silva; Furrier, Max (Revista Brasileira de Geomorfologia, 2023)
The present work aims to propose methodological considerations for the realization of geomorphological mappings focusing on anthropogenic relief forms with the presentation of an example of an integrated legend designed to be used in this type of mapping. The main issues surrounding the realization of geomorphological mapping are discussed, especially those aimed at identifying, classifying, and recording the forms resulting from human action. A broad bibliographic and methodological review of research on anthropogenic geomorphology and on geomorphological mapping under development in Brazil and abroad was carried out. Based on this conceptual and methodological review, this work proposes to create a new methodological proposal for geomorphological mapping with a focus on anthropogenic landforms and an integrated legend.